Ionic fragmentation of a natural product, limonene (C10H16), following core - Castilho, R. B. de; Nunez, C. V.; Coutinho, Lúcia H.; Lago, Alexsandre F.; Bernini, Rafael Berrelho; Souza, Gerardo Gerson Bezerra de (Journal of Electron Spectroscopy and Related Phenomena, 2007)
Photoionization of the limonene [C10H16] molecule was studied for the first time following C 1s ionization, using synchrotron radiation and time-of-fight mass spectrometry. As a reference for further analysis of the photon induced fragmentation of the limonene molecule, the He(I) mass spectrum was also obtained. Previously unreported singly charged species have been observed at 310 eV: H+, C+, CH+, CH2 +, CH3 +. A close similarity has been observed between the high photon energy mass spectrum and the standard electron impact mass spectrum of limonene, obtained at 70 eV. In particular, the base peak [C5H8 +, m/q = 68], known to result from a Retro Diels-Alder reaction, remains the same in both cases. Approximate values for the mean kinetic energy were determined for all ionic species. © 2006 Elsevier B.V. All rights reserved.
C 1s] photoionization
Keywords: Kinetic Energy; Mass Spectrometry; Photoionization; Photons; Reaction Kinetics; Synchrotron Radiation; Core Ionization; Electron Impact Mass Spectrum; Limonene; Time-of-flight Mass Spectrometry; Organic Compounds